1999
DOI: 10.1021/es9900297
|View full text |Cite
|
Sign up to set email alerts
|

Identification of New Drinking Water Disinfection Byproducts Formed in the Presence of Bromide

Abstract: Using a combination of mass spectrometry and infrared spectroscopy, disinfection byproducts were identified in ozonated drinking water containing elevated bromide levels and in ozonated water treated with secondary chlorine or chloramine. Only one brominated byproductdibromoacetonitrilewas found in the water treated with only ozone. This compound was found only in one of the three treatment rounds and was also present in the untreated, raw water but at levels 20 times lower than in the ozonated water. Many m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
78
0
2

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 150 publications
(83 citation statements)
references
References 12 publications
3
78
0
2
Order By: Relevance
“…Although there are obvious differences among the endpoints among the assays, these results suggest that S. typhimurium cannot quantitatively predict the relative cytotoxic or genotoxic risk of DBPs in mammalian cell systems. Bromate is of concern because when present in raw waters it can cause the generation of brominated DBPs after disinfection processes [Richardson et al, 1999]. The U.S. EPA regulated bromate in drinking water as a probable human carcinogen based on animal data [EPA, 1998].…”
Section: Discussionmentioning
confidence: 99%
“…Although there are obvious differences among the endpoints among the assays, these results suggest that S. typhimurium cannot quantitatively predict the relative cytotoxic or genotoxic risk of DBPs in mammalian cell systems. Bromate is of concern because when present in raw waters it can cause the generation of brominated DBPs after disinfection processes [Richardson et al, 1999]. The U.S. EPA regulated bromate in drinking water as a probable human carcinogen based on animal data [EPA, 1998].…”
Section: Discussionmentioning
confidence: 99%
“…Trihalomethanes (THM) were the first to be identified and are most abundant organic DBP in chlorinated water [1,2]. In addition to THM numerous compounds have been identified after application of chlorine and ozone-based chemicals [3,4]. A mass balance taking into account known DBP reveals that approximately 50% of halogenated DBP are missing compared with the total organic halogen (TOX) and, after ozone application, approximately 40% of oxidized DBP are missing compared with the assimilable organic carbon (AOC) [5].…”
Section: Introductionmentioning
confidence: 99%
“…However, in low bromide waters, such as those typically encountered in central Arizona, chlorinated species tend to dominate (Richardson et al, 1999). In this study, the maximum bromide concentration observed was 32 lg L À1 , which substantially limited the formation of brominated DBPs.…”
Section: Dbp Precursorsmentioning
confidence: 57%